Gestantes de risco atendidas na Rede Mãe Paranaense : prematuridade e óbito neonatal - Demitto, Marcela de Oliveira (2015)
The high-risk pregnancy increases the probability of an adverse evolvement, both of the mother and the fetus, and it is often responsible by high rates of premature birth and neonatal death. These events are considered public health problems worldwide and important indicators of maternal and child health. The objective of the research was to evaluate factors associated with prematurity and neonatal mortality of children born in hospitals, through the monitoring of pregnant women at high risk ambulatory of Parana´s Mother Network. This is an epidemiological, cross-sectional study of documentary basis, conducted with children born of mothers assisted by the high risk ambulatory of a philanthropic hospital in Maringá from September 2012 to September 2013. Data were collected between May and August 2014, through the medical records of pregnant women, newborn´s birth certificate and death certificate. The collected data were entered into spreadsheet Microsoft Office Excel 2010® and processed using the Statistica 7.1 program and Epi Info 3.5.2. In order to search the association between the dependent variables (preterm birth and neonatal death) and the independent, gross analysis, Odds Ratio and chi-square were applied. It was utilized multivariate analysis by logistic regression, with a significance level of 5% and 95% confidence interval. It was also employed spatial analysis with data on prematurity of the 30 municipalities that are part of the 15 Health Regional of Paraná, through the Exploratory Spatial Data Analysis. The prevalence of preterm birth was 19.1%. The multivariate analysis showed that women with moderate to severe hypertension and hypothyroidism have less chance of premature birth. The variables: preterm labor in a previous pregnancy and multiple pregnancy were associated with premature birth. The scoring method for scheduling consultations did not allow the prediction of prematurity. Among the different socioeconomic and demographic indicators analyzed, two variables presented spatial association with prematurity: distance from the reference center for treatment of high risk pregnancies and unemployment rate, with positive spatial autocorrelation (I = 0.2156, p = 0.012) and (I = 0.1877, p = 0.016), respectively, indicating that the greater the distance of the mother´s residence and also unemployment, the higher the rate of preterm infants. The neonatal mortality coefficient was 17.7 deaths/1.000 live births, most of them occurring in the early neonatal period (76.9%). The multivariate analysis demonstrated that the preterm labor, fetal malformation and multiple pregnancy were the clinical complications associated with neonatal death. Premature newborns, with very low birth weight and Apgar score lower than 7 at 5 minutes after delivery presented high risk of death. In conclusion, the identification of risk factors for preterm birth and neonatal mortality may help in the planning of actions for the perinatal network consolidation, with the restructuring and qualification of the assistance processes in the prenatal of high risk pregnancies, childbirth and newborn care.